Comparison of respiratory muscle activities and cardiovascular function during different breathing types in healthy adults: Costal breathing, flow incentive spirometry, and volume incentive spirometry - Preeyaphorn Songsorn; Kanyapit Chummee; Chutima Yaanan; Anurak Banlueharn; Kornanong Yuenyongchaiwat; Chalearmpong Pinupong; Sasipa Buranapuntalug (PLoS ONE, 2025)
Background Various breathing exercises are used to enhance lung function. However, many patients have reported experiencing breathlessness and an increased work of breathing during their use, but evidence supporting this is limited. This study aimed to compare respiratory muscle activity and cardiovascular function during different breathing exercises. Methods Forty-five healthy adults participated in this study. They were randomly assigned in a crossover design involving three breathing techniques: flow incentive spirometry, volume incentive spirometry, and costal breathing exercises with sustained maximal inspiration. Respiratory muscle activity (sternocleidomastoid, superior external intercostal, and inferior external intercostal) and cardiovascular function were assessed during each technique at baseline and during the 3rd, 6th, and 9th breaths. Results Sternocleidomastoid, superior external intercostal, and inferior external intercostal were more activated during flow incentive spirometry and volume incentive spirometry than during costal breathing exercises with sustained maximal inspiration. During flow incentive spirometry, stroke volume and heart rate significantly increased, while cardiac output significantly decreased compared to volume incentive spirometry and costal breathing exercises with sustained maximal inspiration throughout the 10 breathing cycles. Conclusion Flow incentive spirometry and volume incentive spirometry elicited greater accessory muscle activity than costal breathing exercises with sustained maximal inspiration. Inferior external intercostal was activated in all breathing techniques. In particular, flow incentive spirometry stimulated changes in cardiovascular function more than volume incentive spirometry and costal breathing exercises with sustained maximal inspiration. Therefore, volume incentive spirometry and costal breathing exercises with sustained maximal inspiration are recommended to minimize breathing effort and cardiovascular instability.